O Sistema de Inovação em São Carlos sob uma abordagem sistêmica e a análise de redes - Piekarski, Ana Elisa Tozetto (2007)
São Carlos City comprises a set of organizations that have some kind of relationship (formal or informal, rare or intense) among themselves and with local companies, thus being one of the São Paulo State Technology Pole. In the city, there are actors responsible for the knowledge production: the scientific institutional environment is responsible for 5.3% of national scientific production. Edquist (2004) defines an Innovation System (IS) from the determinants of innovation process: all important economic, social, political, organizational, institutional, and other factors that influence the development, diffusion, and use of innovations (p. 182). Considering the dynamic of the set of organizations existing in São Carlos as an innovation system, this thesis characterizes the articulation between the parts of this system. The analysis framework includes IS concepts with locational (national, supra-national, regional) or sectorial basis, searching for topics in the systemic approach proposed by Edquist and in the social network theory to map the relationship among the agents of the innovation process. The main contribution of this work is the quantitative and qualitative characterization of the innovation process activities in São Carlos, in a systemic approach, including: research and development, education, manufacturing, articulation and support, generating of new enterprises, and institutional conformance.